Potential impact of plans and policies based on the principles of conservation agriculture on the control of soil erosion in Brazil. (23rd February 2021) - Polidoro, José Carlos; de Freitas, Pedro Luiz; Hernani, Luís Carlos; Anjos, Lúcia Helena Cunha dos; Rodrigues, Renato de Aragão Ribeiro; Cesário, Fernando Vieira; Andrade, Aluísio Granato de; Ribeiro, Jefé Leão
Abstract: Land use and coverage surveys show that 30.5% of Brazil's territory was dedicated to the production of food, fibers, biofuels, and raw materials. This paper fills a gap and provides information to society and decision‐makers about the effectiveness of the adoption of conservation agriculture (CA) principles with zero tillage (ZT/CA) and integrated crop–livestock–forest (iCLF‐CA) systems as the central policies to mitigate soil erosion, the main agent of land degradation and productivity loss. The increase in CA area by 2030 was estimated using Holt's damped technique for ZT/CA and simple linear models for iCLF‐CA. The annual potential for soil erosion with intensive conventional tillage and monocropping, considering land use and cover in 2017, is 3.0 billion tons. The economic impact, based only on replacement of nutrient losses, is estimated to be 15.7 billion US$ yr −1 . To control soil erosion by water, to intensify agricultural production, and mitigate the greenhouse gas emissions are the goals of the PRONASOLOS, a national program for detailed soil survey and interpretation. The annual economic impact of the adoption of CA principles by controlling soil erosion was estimated at 1.5 billion US$ for ZT/CA in 2017 and 0.5 billion US$ for iCLF‐CA in 2015. The future increase of the CA area was forecast at 34.4 and 25.4 Mha for ZT/CA and iCLF‐CA, respectively. The positive impacts of the adoption of CA principles in Brazil are the result of the determination of farmers, among many actors, and of the effectiveness of government plans and policies.